Transforming Agriculture with IoT in Nepal: Opportunities and Challenges - Bhatt, Prakash Datt (Journal of Durgalaxmi, 2025)
Internet of Things (IoT) has been developing rapidly for the last two decades and its application in diverse fields is increasing the performance and productivity by automation and sensor-based technology. It has been observed that the agriculture sector is using IoT-enabled technologies, viz. sensors, actuators, drones, and ultrasonic devices for automating most of the tasks that can reduce the amount of time; and to increase the overall efficiency and have a better crop yield, by making smarter decisions. Despite the largest portion of GDP in Nepal being contributed via agriculture, the traditional way of farming, lack of contemporary technologies and other infrastructure and crop-raiding animals; people are transforming the occupation and leaving the cultivating land bare. The landscape of the traditional agricultural system can be changed by introducing smart agriculture and precision farming. There are many opportunities for smart agriculture in Nepal, like improving the lifestyle of people and reducing overseas employment with sustainable agricultural development. In contrast, limited development in technology, digital divide and lack of governmental policy may challenge implementation.